Development of e-learning materials for CSA and CIS course modules - Nimusiima, Alex; Nakayiwa, Florence Mayega; Majaliwa, Jackson Gilbert Mwanjalolo (2024)
The report documents the capacity building to CIS/CSA course module developers on translating the course modules into e-learning materials. It also reports the uploading of CSA/CIS modules developed as part of AICCRA into RUFORUM Regional E-Learning Platform. Uploading AICCRA CIS/CSA course modules has improved and strengthened RUFORUM E-Learning Platform.